Linking Exploitative Leadership, Green HRM to OCBE and Emotional Exhaustion Among Gen Z in Jakarta’s F&B Industry - Arafah, Mutiara Jihad; Emilisa, Netania; Aldisa, Syafira; Mariaulfa, Inge (Golden Ratio of Human Resource Management, 2026)
The food and beverage (F&B) industry in Jakarta has experienced rapid growth, but it also contributes significantly to environmental degradation. To address this issue, fostering employees’ voluntary pro-environmental behaviors known as Organizational Citizenship Behavior for the Environment (OCBE) is essential. This study examines the influence of exploitative leadership and Green Human Resource Management (Green HRM) on OCBE, with Emotional Exhaustion serving as a mediating variable among Generation Z employees in South Jakarta’s F&B sector. A quantitative survey method was employed, involving 180 purposively selected respondents. Data were analyzed using Structural Equation Modeling (SEM) and the Sobel test. The findings reveal that while Green HRM significantly enhances OCBE, it also increases Emotional Exhaustion. In contrast, exploitative leadership hurts OCBE but does not significantly affect Emotional Exhaustion. Furthermore, emotional exhaustion significantly reduces OCBE and mediates the relationship between Green HRM and OCBE. These results underscore the importance of maintaining employees’ psychological well-being when implementing environmentally oriented HRM practices. Organizations are encouraged to avoid exploitative leadership styles and to balance the demands of Green HRM with adequate emotional support to optimize OCBE.